Structural Reforms in Southeastern Europe since the Kosovo Conflict - Gressani, Daniela (Washington, DC: World Bank, 2013)
This paper attempts to describe and assess the achievements of the countries of South Eastern Europe - Albania, Bosnia and Herzegovina, Bulgaria, Croatia, FYR Macedonia, Romania, and Federal Republic of Yugoslavia - in pursuing structural economic reforms in the period since the end of the Kosovo conflict. The paper concentrates on four key areas of structural reforms: a) public management and anti-corruption; b) creating a liberal environment for trade in goods and services; c) attracting foreign investments; and d) encouraging the growth of a private market based economy. Since the Kosovo conflict, the countries of Southeastern Europe have made encouraging progress in advancing structural reforms and preparing their economies for greater integration with Europe and the rest of the world with the aim of raising the rate of sustainable economic growth. But progress has been uneven across sectors and across countries. The gap in economic performance with respect to central Europe remains large and can be bridged only with determined reforms in creating the conditions for the formation and growth of private enterprises. Attention must also shift towards strengthening governance and fighting corruption.